Nitrogen and phosphorus fertilisers optimise root morphology and soil nutrients in mixed annual grass and bean sown grassland in alpine regions - Ting-Xu Feng; Fei Li; Xue-Mei Xiang; Wei-Shan Lin; Xi-Jie Wei; Lin Zhang; Ke-Jia De (PLoS ONE, 2025)
The grass-bean hybrid system in alpine regions was an important method to increase the root system and nutrients of grasses, however, there was no clear conclusion from the research on whether the nitrogen——phosphorus fertiliser additions in alpine regions had an enhancement effect on the root system and nutrients of the grass-bean hybrids.Through the establishment of an artificial grass-bean mix in an alpine region at 4,270 meters above sea level, we examined the effects of exogenous fertilizer additions on forage roots and nutrients in an annual grass-legume forage mix system using (fertilizer application: A1~4 vs. mix ratio B1~5).The results illustrate that: the addition of nitrogen and phosphorus did not significantly increase forage nutrients in grass-bean mixtures compared to no fertiliser, which appeared to be more favourable; nitrogen——phosphorus nutrients increased the root length and root projection area of forage, and also increased the nutrient content of the soil.The forage CP, TN, TC, and TP contents as well as the soil nutrient contents gradually increased as the fraction of legume forage increased under various mixing ratios. However, as the percentage of legumes increased, root morphology trended downward, and mixed treatments outperformed the monoculture control.The study’s findings were as follows: In the nitrogen——phosphorus fertilizer addition test of annual grass and bean mixed sowing in alpine areas, nitrogen can increase the surface area and projected area of the root system, while phosphorus can increase the length of the root system and have significant improvement effects on soil nutrients. However, there is no clear benefit in terms of improving the forage’s nutrient content. This could offer direction for choosing fertilizers and improving soil fertility in grasslands that are combined with annual grass and beans.